The Influence of Hospitality Marketing Performance On The Lack of Visitors In The Hospitality Business - Miaty, Indah Juneta; Muslim, Muslim; Ramli, Abdul Haeba (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Hotels are an important part of tourism and a place for anyone to rest. The aim of this research was to determine the influence of facilities, brand image, product quality, promotions and service quality on customer satisfaction and customer loyalty. This type of research is quantitative with a purposive sampling technique distributed through questionnaires to 145 employee respondents to visitors to 4 Star Hotels who live in Tangerang and Bogor. Primary data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of this research show that the 6 (six) proposed hypotheses are accepted, and the promotion variable has the greatest direct influence on customer satisfaction. Based on these findings, it can be seen that the role of facilities, brand image, product quality, promotion and service quality influence customer satisfaction and the level of satisfaction influences customer loyalty in 4 star hotels. Mediationally, it can be seen that the results show negative results for the service quality and service quality variables. product quality on customer loyalty through hotel customer satisfaction.   Keywords: image facilities, product and service quality, promotion, customer satisfaction, customer loyalty